Reappraisal of Anatomic Outcome Scales of Coiled Intracranial Aneurysms in the Prediction of Recanalization - Lee, Jong Young; Kwon, Bae Ju; Cho, Young Dae; Kang, Hyun-Seung; Han, Moon Hee (Journal of Korean Neurosurgical Society, 2013)
Several scales are currently used to assess occlusion rates of coiled cerebral aneurysms. This study compared these scales as predictors of recanalization. Clinical data of 827 patients harboring 901 aneurysms treated by coiling were retrospectively reviewed. Occlusion rates were assessed using angiographic grading scale (AGS), two-dimensional percent occlusion (2DPO), and volumetric packing density (vPD). Every scale had 3 categories. Followed patients were dichotomized into either presence or absence of recanalization. Kaplan-Meier analysis was conducted, and Cox proportional hazards analysis was performed to identify surviving probabilities of recanalization. Lastly, the predictive accuracies of three different scales were measured via Harrell's C index. The cumulative risk of recanalization was 7% at 12-month, 10% at 24-month, and 13% at 36-month of postembolization, and significantly higher for the second and third categories of every scale (p<0.001). Multivariate-adjusted hazard ratios (HRs) of the second and third categories as compared with the first category of AGS (HR : 3.95 and 4.15, p=0.004 and 0.001) and 2DPO (HR : 4.87 and 3.12, p<0.001 and 0.01) were similar. For vPD, there was no association between occlusion rates and recanalization. The validated and optimism-adjusted C-indices were 0.50 [confidence (CI) : -1.09-2.09], 0.47 (CI : -1.10-2.09) and 0.44 (CI : -1.10-2.08) for AGS, 2DPO, and vPD, respectively. Total occlusion should be reasonably tried in coiling to maximize the benefit of the treatment. AGS may be the best to predict recanalization, whereas vPD should not be used alone.